Morphological Spectrum of Excised Conjunctival Lesions in a Tertiary Hospital in North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Conjunctiva is a transparent membrane lining the inner surface of the eyelids and the globe up to the corneoscleral limbus. It is a common site for the growth of lesions in the eye. Depending on their origin, conjunctival lesions could be non-neoplastic and neoplastic. The neoplastic lesions are either benign or malignant. These lesions can be distinguished based on the patient’s history, clinical presentation and histopathological features.Aims:In this study, the pattern of excised conjunctival lesions was determined.Methods and Material:This was a 6-year (2010–2015) retrospective study of all excised conjunctival lesions diagnosed at the Pathology Laboratory of Aminu Kano Teaching Hospital.Statistical analysis used:Data were analysed with Statistical Package for Social Sciences (version 20.0; SPSS, Chicago, IL, USA).Results:A total of 198 conjunctival lesions were diagnosed during the period. The male patients were 136 (68.70%), whereas the females were 62 (31.30%) with male-to-female ratio of 2.2:1, with a mean age ± standard deviation of 37.69 ± 16.39 years. The neoplastic nature of the lesions was as follows: 54 (27.3%) were malignant, 61 (30.8%) were pre-malignant and 83 (41.9%) were benign. The most common lesions observed were conjunctival squamous cell carcinoma, dysplasia and squamous papilloma with frequencies of 50 (25.30%), 46 (23.20%) and 24 (12.10%), respectively.Conclusions:Benign lesions are the most common conjunctival lesions, whereas squamous papilloma and squamous cell carcinoma are the most common benign and malignant lesions, respectively.